Cambiamenti sociali e nuove sfide per la scuola - Viti, Cristina (Chimica nella Scuola, 2025)
What can educational institutions do while facing the challenge of social change? Classes are increasingly composed of students from various origins and diverse linguistic and cultural backgrounds. That implies taking account of the students’ social, emotional and educational needs with personalized learning strategies based on the relationship between pupils and teachers. These one-on-one meetings are held in a welcoming environment where creative and inclusive educational approaches can take place. Scientific programs promoted by CIDI Firenze embody a feasible way to address the issue.